Powers : a Study in Metaphysics. - Molnar, George (Oxford University Press, UK, 2006)
George Molnar came to see that the solution to a number of the problems of contemporary philosophy lay in the development of an alternative to Hume's metaphysics. In this work, which was almost completed when its author died, he developed a thorough account of causal powers and succeeded in producing something both highly focused and at the same time wide-ranging. - ;George Molnar came to see that the solution to a number of the problems of contemporary philosophy lay in the development of an alternative to Hume's metaphysics. This alternative would have real causal powers at its centre. Molna.